Use of elastography for cervical cancer diagnostics - Bakay, O.A.; Golovko, T.S. (Experimental Oncology, 2015)
The aim of the study was to investigate the use of elastography for cervical cancer diagnostics. Materials and Methods: The ultrasonic study with use of sonoelastography involved 87 patients with cervical pathology (cervicitis, n = 11; dysplasia, n = 14; cervical cancer, n = 62). Results: At non-malignant pathology elastic types of elastograms prevailed while the tumors were characterized by images of stiff type formations. Present study has demonstrated an effectiveness of sonoelastography for valuation of tumor process invasion levels. At detection of tumor invasion into parametrium, the test sensitivity increased from 77.1 to 91.4%, specificity — from 85.1 to 96.2%, accuracy — from 80.6 to 93.5%; in case of tumor invasion into vagina these parameters correspondently changed: from 75.0 to 83.3%, from 76.9 to 88.4%, from 75.8 to 85.4%, respectively; and in case of uterus: from 82.9 to 85.3%, from 85.7 to 95.2%, from 83.8 to 88.7%, respectively. Conclusions: Inclusion of elastography into ultrasound examination of cervical pathologies could significantly improve diagnostic quality of the method. Key Words: sonoelastography, ultrasonic diagnostics, cervical cancer.